A Wise Enemy: The Seventeenth-Century Ottoman Portrayal of the Polish Commander Stanisław Żołkiewski - Yıldız, Özlem (IKON, 2022)
Abstract This paper focuses on the visual and textual portrayal of the Polish commander and hetman (highest military officer), Stanislaw Żołkiewski (d. 1620), in an early 17th-century Ottoman illustrated history book, the Şehname-i Nadiri. Żołkiewski’s legendary memory was cemented in Polish history with his depictions in painting and literature. Yet, his depiction in a wellknown Ottoman book has largely escaped scholarly attention. The text of the Şehname-i Nadiri describes Żołkiewski as a wise and influential nobleman before it narrates his death on the battlefield by both lamenting the demise of a nobleman and celebrating the Ottoman victory. A painting of the Battle of Cecora in the same volume emphasizes his high rank and hints at the aftermath of his death. These textual and visual portrayals in the Şehname-i Nadiri offer an insight into representations of the Other in Ottoman historical narratives. Abstract Mudri neprijatelj: osmanski prikaz poljskog zapovjednika Stanisława Żołkiewskog iz sedamnaestog stoljeća Ovaj rad raspravlja o tekstualnom i vizualnom prikazu poljskoga zapovjednika i hetmana (atamana), Stanislawa Żołkiewskog (u. 1620.), u osmanskoj ilustriranoj povijesnoj knjizi iz ranog 17. stoljeća, Şehname-i Nadiri. Sjećanje na Żołkiewskog učvrstilo se u poljskoj povijesti njegovim prikazima u slikarstvu i književnosti. Ipak, njegov lik u poznatoj osmanskoj knjizi uvelike je izbjegao pozornosti znanstvenika. Tekst Şehname-i Nadiri opisuje Żołkiewskog kao mudrog i utjecajnog plemića prije smrti, zatim pripovijeda o njegovoj slavnoj smrti na bojnom polju žaleći zbog smrti plemića i slaveći osmansku pobjedu. Prikaz Bitke kod Cecore u istom djelu naglašava njegov visoki čin i nagovještava posljedice njegove smrti. Ovi tekstualni i vizualni prikazi nude uvid u način prikaza Drugoga u osmanskim povijesnim narativima.